Effect of potassium on growth, yield and economics of safflower (Carthamus tinctorius L.): Effect of potassium on growth, yield and economics of safflower (Carthamus tinctorius L.) - K C OMBASE; S V KHADTARE; S K SHINDE; L N TAGAD; D R MURUMKAR; H N AIWALE; V B AKASHE (Journal of Oilseeds Research, 2020)
Field experiment was conducted for ascertaining the response of safflower to different levels of potassium for three years in post rainy season from 2016-17 to 2018-19. The experiment consisted of five treatments viz., 0, 20, 30, 40 and 50 kg/ha K2O with four replications in RBD. Potassium application @ 50 kg/ha recorded significantly higher seed yield than 40 kg/ha. Plant height and 100- seed weight were also significantly influenced due to potassium.